Tunneling Atomic Force Microscopy of Self-Assembled In(Ga)As/GaAs Quantum Dots and Rings and of GeSi/Si(001) Nanoislands - Filatov, Dmitry; Shengurov, Vladimir; Nurgazizov, Niyaz; Borodin, Pavel; Bukharaev, Anastas (IntechOpen, 2012)
None